PERAN PENDIDIKAN KEWIRAUSAHAAN DALAM MEMBANGUN KARAKTER DAN KEMANDIRIAN SISWA - Asep Saepul Bahri; Khotimah Herliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Amid global competition and economic uncertainty, schools face the challenge of nurturing not only academic competence but also strong character and student independence. This study aims to examine the role of entrepreneurship education in shaping students’ character and self-reliance at the senior secondary level. Using an explanatory quantitative approach, data were collected from 120 Grade IX students in SMA and SMK schools in Depok, West Java, selected via stratified random sampling. Variables were measured using validated instruments and analyzed through descriptive statistics, classical assumption tests, and multiple linear regression using SPSS 26. Results show that entrepreneurship education significantly influences both character (R² = 0.482; p = 0.000) and independence (R² = 0.517; p = 0.000). The regression coefficients indicate strong positive effects (β = 0.695 for character; β = 0.723 for independence). Findings affirm that project-based and experiential entrepreneurship learning effectively fosters traits such as responsibility, creativity, risk-taking, and decision-making—key components of Pancasila Student Profiles.